2018
DOI: 10.1007/s00603-018-1470-9
|View full text |Cite
|
Sign up to set email alerts
|

The Fragmentation Energy-Fan Model in Quarry Blasts

Abstract: This paper investigates fragmentation in an aggregate quarry in the light of the fragmentation-energy fan concept. Six blasts were monitored, located one behind the other in the same quarry area. The rock structure was blocky, the water level and the usage of explosives were variable within and between the blasts; however, the distribution of explosive energy in the blocks was relatively uniform and the performance of both explosives per unit mass appeared to be similar. The powder factor above grade was betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…This model was developed by Ouchterlony and coworkers (Ouchterlony et al 2017(Ouchterlony et al , 2021Ouchterlony and Sanchidrián 2018;Segarra et al 2018;Sanchidrián et al 2022). Sieving data obtained from tests with different values of specific charge q may be written where x P is the size at the percentage passing P. The exponent = (P) or P is, for a given blast geometry in a given material, a function of P only.…”
Section: The Fragmentation-energy Fanmentioning
confidence: 99%
See 2 more Smart Citations
“…This model was developed by Ouchterlony and coworkers (Ouchterlony et al 2017(Ouchterlony et al , 2021Ouchterlony and Sanchidrián 2018;Segarra et al 2018;Sanchidrián et al 2022). Sieving data obtained from tests with different values of specific charge q may be written where x P is the size at the percentage passing P. The exponent = (P) or P is, for a given blast geometry in a given material, a function of P only.…”
Section: The Fragmentation-energy Fanmentioning
confidence: 99%
“…However, when fragment sizes are sought in an absolute, quantitative or predictive fashion, image analysis alone cannot provide a solution. Combinations of image analysis with on-site sieving, or derivation of rock cuts weights from crushing plant mass flows, have been used with advantage (Cho et al 2003;Ouchterlony et al 2006Ouchterlony et al , 2010Segarra et al 2018). 9 Concluding Remarks 1.…”
Section: Measurement Of Fragmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fragmentation and environmental effects are influenced by the amount of powder factor [21], [22]. A higher amount of powder factor improves fragmentation and, thus, productivity [23]. Nevertheless, the blast-induced vibration and airblast also increase with an increase in the powder factor [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Segarra et al [23] investigated the effects of powder factor on different percentage passing and concluded that fragmentation improves with powder factor. The most common tool for evaluating the impacts of blasting on structures and human beings is the Peak Particle Velocity (PPV) [26]- [29], as shown in Equation 1 [30], [31].…”
Section: Introductionmentioning
confidence: 99%